Solidarity communication and consumption in the digital territory.: Analysis of the digital communication of solidarity marketers in the Autonomous City of Buenos Aires, Argentina - Fernández Miranda, Rodrigo (Cooperativismo & Desarrollo, 2022)
This article aims to describe the first results of the survey of cooperatives and mutuals in the province of Santa Fe, Argentina, carried out within the framework of the Associative Ecosystem Observatory of said territory. In this sense, not only does it seek to narrate the experience of structuring this organization and specify the methodological aspects involved to monitor the associative phenomenon, but it also seeks to provide a synthesis of the main features assumed by the dynamics of the cooperatives and mutuals, in particular, their distribution in the territory, the diversity of social objects and some continuities and ruptures in their historical evolution.
Keywords: social and solidarity economy; digital communication; marketing; solidarity consumption; territorial development